Evaluating the efficacy of closing the current European network of marine protected areas to mobile bottom-contacting fishing gears - Karin J. van der Reijden; Sebastian Valanko; Jochen Depestele; Joanna Desmidt; José M. González Irusta; Jan Geert Hiddink; Pascal Laffargue; Marija Sciberras; P. Daniel van Denderen (Biological Conservation, 2026)

Assessment of Bottom Trawl Impacts on the Status of Seabed Communities in European Seas - Jan Geert Hiddink; Sebastian Valanko; Luke Batts; Esther D. Beukhof; Mats Blomqvist; Stefan Bolam; Belén Calero; Michele Casini; Marina Delgado; Jochen Depestele; Joanna Desmidt; Gabriele Di Bona; et al. (Fish and Fisheries, 2026)
Bottom trawling affects seabed habitats, but its large‐scale impacts remain poorly quantified. Assessment of trawling impacts is essential to support monitoring and achieving sustainability objectives under international conventions, sustainable development goals, and seafood certification programs. We present a Europe‐wide quantitative assessment of bottom trawling impacts, accounting for regional seabed‐community sensitivity drivers, across the Baltic, Atlantic, Mediterranean and Black Sea continental shelves. Using two risk‐based indicators of seabed status—Relative Benthic Status determined as benthic community biomass relative to seabed fauna carrying capacity (RBS tot ) and RBS sen (biomass of the 10% most sensitive fauna relative to carrying capacity)—we found substantial regional and habitat differences. The Black, Baltic and Aegean‐Levantine Seas showed low trawling intensity and high seabed status across habitats. In contrast, the Western Mediterranean, Ionian and Central Mediterranean and Adriatic Seas were the most severely impacted. Trawling affected the sensitive species biomass fraction more strongly than the total community biomass. RBS tot was in good condition (here chosen as RBS > 75% for epifauna) for over 79% of habitat‐ecoregion combinations. In contrast, RBS sen met this threshold in only 46% of these. A strong correlation emerged between the mean trawling intensity and RBS tot and RBS sen , allowing the use of SAR to estimate ecosystem status. This relationship can support decisions on where, and by how much, SAR reductions are needed to achieve good environmental status in regions where no detailed assessment is available. Our approach provides a quantitative framework to balance fishery production with ecosystem sustainability, offering tools for environmental and fisheries management in Europe.

Benthic food resources and the condition of bentho-demersal fish: spatial trends and relationships in the northern shelf of the Bay of Biscay - Thomas Outrequin; Hubert du Pontavice; Jérôme Guitton; Pauline Boët; Jacques Grall; Pascal Laffargue; Hervé Le Bris (Estuarine, Coastal and Shelf Science, 2025)

Challenges of reusing marine image-based data for fish and benthic habitat Essential Variables: insights from data producers - Dominique Pelletier; Jacquomo Monk; Franziska Althaus; Catherine Borremans; Melissa Hanafi-Portier; Ben Scoulding; Karine Olu; Candice Untiedt; Chris Jackett; Neville Barrett; Pascal Laffargue; Sandrine Vaz; et al. (Frontiers in Marine Science, 2025)
Understanding the status and trends of Essential Ocean Variables (EOV) and Essential Biodiversity Variables (EBV) is crucial for informing policy-makers and the public about sustainable management of marine biodiversity. Marine image data hold significant potential in this context, offering a permanent, information-rich and non-extractive record of marine environments at the time of capture. Quantitative image-based measurements such as species abundance and distribution have proven to be highly effective for engaging diverse stakeholders. The exchange and reuse by experienced fisheries scientists and marine ecologists of nine image-based datasets (including images, metadata and annotations) collected through various protocols revealed a substantial disconnect between initial expectations and actual practical usability, particularly in terms of understanding and reusing data. Two key issues were highlighted. First, the link between the datasets and their potential applications in deriving EOV/EBV was often inadequately described or absent. Second, despite both initial and ongoing efforts to document the data, new users continued to face challenges in understanding underlying properties and contextual features of datasets. We suggest these findings are likely to characterize many, if not most, historical image-based datasets. While standards promoting the FAIR principles (Findable, Accessible, Interoperable, and Reusable) for image-based data are emerging, our focus here is on the specific features of documentation that enable or facilitate reuse of data for the purpose of deriving EOV/EBV. From this perspective, we provide a set of recommendations for documenting both images and their associated annotations, aimed at supporting broader applications of in situ image data in marine conservation and ecology.

Mesoscale assemblages of fish and megainvertebrates as evidence of benthiscapes on continental shelves - Thomas Outrequin; Hervé Le Bris; Jacques Grall; Pascal Laffargue (Journal of Marine Systems, 2025)

Trawling-induced change in benthic effect trait composition – A multiple case study - Olivier Beauchard; Clare Bradshaw; Stefan Bolam; Justin Tiano; Clément Garcia; Emil De Borger; Pascal Laffargue; Mats Blomqvist; Irini Tsikopoulou; Nadia K. Papadopoulou; Christopher J. Smith; Jolien Claes; et al. (Frontiers in Marine Science, 2023)
Introduction The importance of the response-effect trait dichotomy in marine benthic ecology has garnered recent attention. Response traits, characterising species responses to environmental variations, have been a dominant focus in the development of ecological indicators for ecosystem health assessment. In contrast, effect traits, expressing effects of organism activities on the ecosystem, still do not benefit from an equal interest in spite of the complementary facet that they provide to complete our understanding of functional diversity and ecosystem vulnerability. In this study, we explore the consequences of disturbance by bottom trawl fisheries on benthic effect trait composition. Methods To this end, we used different contexts of environmental and trawling conditions from thirteen case studies in European waters and apply the same analytical procedure to derive a gradient that solely account for trawling-induced disturbance (Partial RLQ analysis). Results Bottom trawling was found to be a selective force of benthic effect trait composition in a majority of case studies. In general, tube-dwelling species were more typical of low trawling frequencies, whereas deep burrowing species were more resistant at high trawling frequencies. Although we report significantly deleterious effects of trawling on benthic ecosystem functions, the effect trait pattern along the gradient was never related to life span, a key response trait generally assumed to express recoverability following disturbance. Furthermore, we show that trends in species multi-functionality and community functional diversity can be negative or positive along the trawling intensity gradient. Discussion We discuss the relevance of these results in light of recent developments in the framework of response and effect trait dichotomy, and provide guidelines of trait data analysis in the context of trawl fisheries impact on the sea floor. Our findings emphasize the importance of fundamental concepts from functional ecology in this context and represent a first step toward an assessment of trawling effect more oriented on benthos-mediated biogeochemical processes.

Technological innovations to reduce the impact of bottom gears on the seabed - Antonello Sala; Jochen Depestele; Aysun Gümüş; Pascal Laffargue; J. Rasmus Nielsen; Hans Polet; Chris J. Smith; Mustafa Zengin; Francois Bastardie; Ole R. Eigaard; Katell G. Hamon; Frank Jensen; et al. (Marine Policy, 2023)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Influence of bottom trawling on sediment resuspension in the ‘Grande-Vasière’ area (Bay of Biscay, France) - Baptiste Mengual; Florence Cayocca; Pierre Le Hir; Robin Draye; Pascal Laffargue; Benoit Vincent; Thierry Garlan (Ocean Dynamics, 2016)